2021
DOI: 10.1073/pnas.2111101118
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous helielectric nematic liquid crystals: Electric analog to helimagnets

Abstract: Recently, a type of ferroelectric nematic fluid has been discovered in liquid crystals in which the molecular polar nature at molecule level is amplified to macroscopic scales through a ferroelectric packing of rod-shaped molecules. Here, we report on the experimental proof of a polar chiral liquid matter state, dubbed helielectric nematic, stabilized by the local polar ordering coupled to the chiral helicity. This helielectric structure carries the polar vector rotating helically, analogous to the magnetic co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 50 publications
1
75
0
Order By: Relevance
“…3 Structural variants of RM734 temperatures (1C) are on cooling from the isotropic liquid. 5,18,20,28 A green and red arrows indicate increased and decreased T NF-N relative to the parent material, respectively, while a black dash indicates the absence of the N F phase.…”
Section: Materials and The Incidence Of The N F Phasementioning
confidence: 99%
See 2 more Smart Citations
“…3 Structural variants of RM734 temperatures (1C) are on cooling from the isotropic liquid. 5,18,20,28 A green and red arrows indicate increased and decreased T NF-N relative to the parent material, respectively, while a black dash indicates the absence of the N F phase.…”
Section: Materials and The Incidence Of The N F Phasementioning
confidence: 99%
“…28 Imrie et al also reported a number of RM734 derivatives with alternate lateral groups, including the ( S )-2-methylbutoxy group which leads to the chiral N F phase, 20 with this material also being reported independently by others. 18 Again, the increased steric bulk of these lateral groups depresses T NF-N when compared to the parent material. Aya et al synthesised materials in which the lateral unit is positioned to the central phenyl ring, all of which generate the N F phase with a modest reduction in T NF-N .…”
Section: Materials and The Incidence Of The Nf Phasementioning
confidence: 99%
See 1 more Smart Citation
“…28 Imrie et al also reported a number of RM734 derivatives with alternate lateral groups, including the (S)-2-methylbutoxy group which leads to the chiral NF phase, 20 with this material also being reported independently by others. 18 Again, the increased steric bulk of these lateral groups depresses TN F -N when compared to the parent material. Aya et al synthesised materials in which the lateral unit is positioned to the central phenyl ring, all of which generate the NF phase with a modest reduction in TN F -N. 28 Use of azo or nmethylamide linking units eliminates the NF phase entirely, and also the nematic phase in the case of the amide.…”
Section: Archetypal Materialsmentioning
confidence: 99%
“…Figure 3:Structural Variants of RM734 temperatures (°C) are on cooling from the isotropic liquid 5,18,20,28. A green and red arrows indicate increased and decreased TNF-N relative to the parent material, respectively, while a black dash indicates the absence of the NF phase.…”
mentioning
confidence: 99%